Design and analysis of steering knuckle of hybrid metal matrix composite for the fsae vehicle. (2021) - Gupta, Harshit; Shan,; Rajvardhan,; Singh, Nishant K.
Abstract: The steering knuckle is one of the critical and bulky components of the formula society of automotive engineers (FSAE) car. In the FSAE weight of the vehicle is the main objective concern, therefore, the aim is to redesign the upright by using hybrid metal matrix composite material so that factor of safety (FOS) remains larger than two but the weight of the component decreases. The aluminum alloy 7075-T6 is reinforced with silicon carbide and the magnesium powder is used for the preparation of a composite. Static structural analysis of the steering knuckle made of Al-10 wt% SiC-1 wt% Mg was performed using the ANSYS18.1 workbench. The outcomes of the steering knuckle produced of hybrid MMC with improved construction were compared with the results of the old aluminum alloy steering knuckle on the grounds of the real loading cases working under dynamic conditions. From this structural study, it is found that the lower wishbone mount of the knuckle has the highest stress and deflection during service. Cross sectional knuckle area was analyzed and geometrically optimized for maximum shear / maximum stress. The fatigue life and FOS of the hybrid MMC knuckle is investigated in the worst case of testing. The findings obtained from the analytical and FEA study are highly favourable for the changed design with MMC.